Tales of literacy for the 21st century / 2016. - Wolf, Maryanne (The literary agenda, 2016)
Tales of Literacy for the 21st Century wrestles with critical, timely questions for twenty-first century society. How does literacy change the human brain? What does it mean to be a literate or a non-literate person? In the present digital culture what will be lost in the present reading brain, and what will be gained with different mediums than print? By both using research from cognitive neuroscience, psycholinguistics, child development, and education, and considering literacy examples from world literature, Maryanne Wolf plots a course that seeks to preserve the deepest forms of reading from the past, while developing the cognitive skills necessary for this century's next generation around the world.